Accumulator, Transporter, Substrate, and Reactor: Multidimensional Perspectives and Approaches to the Study of Bark - Ponette-González, Alexandra G. (Frontiers in Forests and Global Change, 2021)
Woody ecosystems have a relatively thin but aerially extensive and dynamic layer of bark that, like leaves, regulates material exchange at the interface of air, water, and biota. Through interception, retention, and leaching of materials and interactions with epiphytic communities, bark alters the chemistry and composition of water draining over its surface during precipitation. This mini-review explores different perspectives and approaches to the study of bark and what they reveal about the myriad ways bark surfaces influence the quality of sub-canopy precipitation. Observational studies conducted over the past five decades in the fields of environmental science, ecohydrology, epiphyte ecology, and microbiology demonstrate that bark is an accumulator, transporter, substrate, and reactor. Bark passively accumulates materials from the atmosphere, water, and canopies, and also serves as an active transport surface, exchanging materials laterally and longitudinally. In addition, bark substrates influence epiphyte diversity, composition, and distribution, which, in turn, affect material cycling. Bark surfaces are dynamic over time, changing in response to disturbances (e.g., insect outbreaks, aging, and tree death)—how such changes influence the chemical and elemental composition of throughfall and stemflow merits further study. Moving forward, integration of diverse perspectives and approaches is needed to elucidate the influence of bark surfaces on solute and particulate transport and cycling within woody ecosystems.